The Effects of Dose Rhizoctonia Binucleat (BNR) and Phosphorus to Nitrate Reductase Activity (NRA) and Chlorophyll of Vanilla Seedling (Vanilla planifolia Andrews) - Haryuni Haryuni; Tyas Soemarah Kurnia Dewi (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Vanilla (Vanilla planifolia Andrews) is one of the important exported commodities in Indonesia. Indonesia is one of top five major vanilla exporters in the world, that produce the high quality of Indonesian vanilla with high vanillin content (2.75%). The aims of this research were to determine the effects of dose binukleat Rhizoctonia (BNR) and phosphorus as well as the interaction of the nitrate reductase activity (NRA) and chlorophyll of the vanilla seedling (Vanilla planifolia Andrew). Method in this research used completely randomized factorial design, by involving two factors (dose of BNR inoculation and Phosphor). The first factor is without inoculation and inoculation BNR (M0, M1, M2, M3) wich consists of (0,5, 10, 15) g/polybag, the second factor is the dose of phosphorus fertilizer (P0, P1, P2, P3) which consists of (0, 3, 6, 9) g/polibag. The results showed that the inoculation dose of BNR and doses of phosphorus not significant and lower levels of NRA and chlorophyll while the interaction dose of BNR and phosphorus significantly and increase levels of NRA and chlorophyll of vanilla seedling. Nitrate Reductase Activity and chlorophyll has important role in metabolism process as a plant growth indicator.How to CiteHaryuni, H., Dewi, T. S. K. (2016). The Effects of Dose Rhizoctonia Binucleat (BNR) and Phosphorus to Nitrate Reductase Activity (NRA) and Chlorophyll of Vanilla Seedling (Vanilla planifolia Andrews). Biosaintifika: Journal of Biology Biology Education, 8(2), 141-147.